Measuring The Attractiveness Of Property Issuers: An Empirical Study Of Factors Determining Company Value (2021-2024) - Novita Wulandari; R Taufik Hidayat; Dian Widiyati (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2025)
Abstract: This study aims to determine the effect of Company Growth, Liquidity, Company Size and Profitability on Firm Value. Purpose: This study uses quantitative data, the sample in this study were Property & Real Estate sector companies listed on the Indonesia Stock Exchange in the 2021-2024 period, totaling 44 companies. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings: The results of this study indicate that the Company Growth variable has a positive and statistically significant effect on Firm Value, Liquidity has a negative and statistically insignificant effect on Firm Value, Company Size has a negative and statistically significant effect on Firm Value, Profitability has a positive and statistically insignificant effect on Firm Value. Originality/value: This study discusses Company Value and other factors such as Company Growth, Company Size Liquidity and Profitability which focus on Property & Real Estate sector companies